Development of a scale to evaluate negative menstrual attitudes among Nepalese women - Rina Kawata; Masayuki Endo; Shiba Kumar Rai; Kazutomo Ohashi (BMC, 2022)
Plain Language Summary For sexually mature women, menstruation may be considered burdensome, but its absence may also be a source of concern. Perceptions regarding menstruation are collectively referred to as menstrual attitudes. Previous studies have reported that negative menstrual attitudes are associated with various reproductive health issues in women and vary according to social and cultural backgrounds. To adequately evaluate negative menstrual attitudes among Nepalese women (20-45 years old), we developed a 15-item scale that considers their cultural background and literacy. We observed that attitudes toward menstruation among Nepalese women consisted of three emotions: one positive emotion, including "menstruation is a natural phenomenon", and two negative emotions, including "menstruation is debilitating" and "menstruation is bothersome". In several developing countries, menstruating women are considered unclean, and various restrictions are imposed on women during menstruation (traditional menstrual practices). Nepalese women with strong negative menstrual attitudes, as assessed by our scale, engaged in several traditional menstrual practices with higher frequency. We also observed that women with more negative menstrual attitudes presented with more severe menstrual pain. Our scale was developed to be compatible with the values and literacy of Nepalese women and was easy to answer. We believe that reducing negative emotions toward menstruation will contribute to reducing the frequency of traditional menstrual practices and menstrual pain, thereby facilitating school attendance and entry into the workforce among women in Nepal.